(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Family planning is a critical component of Serbia’s population strategy, as the country’sdemographic trends are rapidly deteriorating. The purpose of this study was to investigate the disparitiesin family planning between rural and urban Serbian women. As a cross-sectional research on arepresentative sample of Serbia’s population, the 2006 National Health Survey was used as the basis forthis study. As a means of contraception, condoms were used by a higher percentage of the respondentswho were younger, better-educated, more financially secure, and did not have any children. We foundthat urban and rural women’s use of family planning differed, although these discrepancies might beattributed to disparities in age and education.